Management of patients with suspected bladder cancer in general practice – diagnostic algorithm and recommendations - Kamecki, Hubert; Mastalerz-Migas, Agnieszka; Sosnowski, Roman; Stelmach, Jerzy; Stelmach, Paweł; Bronisz-Budzyńska, Iwona; Dziurda, Dominik; Zaczyk, Jakub; Drewa, Tomasz (Lekarz POZ, 2025)
In this article, we outline the recommended approach to patients with suspected bladder cancer presenting to primary health care physicians, with particular emphasis on the diagnostic algorithm and criteria for urgent referral to a urology clinic. The clinical characteristics of patients diagnosed with bladder cancer are described, with special attention to hematuria as the most common presenting symptom. Risk factors such as cigarette smoking and specific occupational exposures are summarized, together with the importance of maintaining a high index of suspicion for cancer. Diagnostic options available within the primary health care setting are discussed. The principles of prompt referral using the DiLO system are explained, along with the key aspects of cooperation between family physicians and urologists within a standardized diagnostic pathway. The proposed scheme was developed by an expert board of the Polish Urological Association, based on the European Association of Urology guidelines, and has been endorsed by the Polish Society of Family Medicine and the Porozumienie Zielonogórskie. The aim of this work is to facilitate early detection and shorten the time to treatment initiation through standardization of diagnostic procedures in primary health care.